ANALYZING THE IMPACT OF YOUTUBE MICROLEARNING VIDEOS ON STUDENTS’ VOCABULARY DEVELOPMENT AND THEIR PERCEPTIONS OF ITS USE: A MIXED-METHOD STUDY - Rahmah, Aulia; Siti Maysuroh; Astrid Dwimaulani; Ari Prasetyaningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vocabulary mastery is a fundamental element for English as a Foreign Language (EFL) learners to comprehend and communicate effectively. Recently, digital microlearning has emerged as a popular strategy to facilitate flexible, accessible, and highly focused language learning. Accordingly, this study aims to investigate the perceived impact of YouTube microlearning videos on students’ vocabulary development and explore their perceptions of its use as an instructional medium. This research employed a mixed-methods design involving students from the English Language Education Program at Hamzanwadi University. Data were gathered through a 25-item Likert-scale questionnaire (N=15) and semi-structured interviews (N=10) via purposive sampling. The quantitative results revealed a high perceived impact on vocabulary development (construct mean = 3.84), with significant improvements in word recognition, meaning comprehension, and pronunciation. However, students’ productive speaking confidence developed slower than their receptive skills. Furthermore, participants held a highly positive perception of the medium (construct mean = 3.73), valuing its flexibility, concise duration, and multimedia design, although infrastructural constraints like internet connectivity occasionally challenged its practical utility. In conclusion, YouTube microlearning is a highly effective supplementary tool for receptive vocabulary acquisition, but it requires active pedagogical integration with productive classroom tasks to fully bridge the gap between passive recognition and active usage.